Cost effectiveness of support for people starting a new medication for a long term condition through community pharmacies: an economic evaluation of the New Medicine Service (NMS) compared with normal practice - Elliott, Rachel A.; Tanajewski, Lukasz; Gkountouras, Georgios; Avery, Anthony J.; Barber, Nick; Mehta, Rajnikant; Boyd, Matthew J.; Latif, Asam; Chuter, Antony; Waring, Justin (Springer, 2017)
Background: The English community pharmacy New Medicine Service (NMS) significantly increases patient adherence to medicines, compared with normal practice. We examined the cost-effectiveness of NMS compared with normal practice by combining adherence improvement and intervention costs with the effect of increased adherence on patient outcomes and healthcare costs.